The Proletarian Dream : Socialism, Culture, and Emotion in Germany, 1863-1933 - Hake, Sabine (Interdisciplinary German cultural studies, 2017)
The proletariat never existed--but it had a profound effect on modern German culture and society. As the most radicalized part of the industrial working class, the proletariat embodied the critique of capitalism and the promise of socialism. But as a collective imaginary, the proletariat also inspired the fantasies, desires, and attachments necessary for transforming the working class into a historical subject and an emotional community. This book reconstructs this complicated and contradictory process through the countless treatises, essays, memoirs, novels, poems, songs, plays, paintings, photographs, and films produced in the name of the proletariat. The Proletarian Dream reads these forgotten archives as part of an elusive collective imaginary that modeled what it meant--and even more important, how it felt--to claim the name "proletarian" with pride, hope, and conviction. By emphasizing the formative role of the aesthetic, the eighteen case studies offer a new perspective on working-class culture as a oppositional culture. Such a new perspective is bound to shed new light on the politics of emotion during the main years of working-class mobilizations and as part of more recent populist movements and cultures of resentment